2022
DOI: 10.3389/fpls.2022.829566
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of a Vigor QTL in Chickpea (Cicer arietinum L.) Reveals a Potential Role for Ca4_TIFY4B in Regulating Leaf and Seed Size

Abstract: Plant vigor is a complex trait for which the underlying molecular control mechanisms remain unclear. Vigorous plants tend to derive from larger seeds and have greater early canopy cover, often with bigger leaves. In this study, we delimited the size of a major vigor quantitative trait locus (QTL) on chickpea chromosome 4–104.4 kb, using recombinant association analysis in 15 different heterogeneous inbred families, derived from a Rupali/Genesis836 recombinant inbred line population. The phenotypic and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Further, FRIGIDA gene upregulates the expression of the FLOWERING LOCUS C and accelerates transition to flowering after vernalization (Li et al., 2018). Another gene, TIFY 4B‐like isoform X4, present in plant vigor QTLs was reported to enhance the seed size and leaf size in chickpea (Nguyen et al., 2022). In addition, a recent study in chickpea also reported that a non‐synonymous substitution in the transcription factor CaTIFY4b regulates seed weight and organ size in chickpea (Barmukh et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further, FRIGIDA gene upregulates the expression of the FLOWERING LOCUS C and accelerates transition to flowering after vernalization (Li et al., 2018). Another gene, TIFY 4B‐like isoform X4, present in plant vigor QTLs was reported to enhance the seed size and leaf size in chickpea (Nguyen et al., 2022). In addition, a recent study in chickpea also reported that a non‐synonymous substitution in the transcription factor CaTIFY4b regulates seed weight and organ size in chickpea (Barmukh et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Chickpea has a QTL hotspot for seed size, leaf size, drought responses, and other “Vigour” traits. Nguyen and colleagues have recently fine mapped this QTL [ 265 , 266 ] showing it to be due to variation in a TIFY gene, which mutant studies in Arabidopsis have shown to impact seed size. Natural variation at this locus suggests it contributes significantly to a seed-size number trade-off, among parents that also differ in seed protein content.…”
Section: Fundamental Constraints On Seed Protein Contentmentioning
confidence: 99%
“…Inactivation of SAMBA in Arabidopsis increases leaf growth by stimulating cell division (Eloy et al, 2012), but in maize, the samba mutant has restricted growth causing the formation of stunted plants, most likely by an excess of cell division late during development (Gong et al, 2022a). Some growth-regulatory networks only operate in Eudicots and not in monocots, such as the PEAPOD-KIX-TOPLESS repressor complex (Schneider et al, 2021) that restricts growth during the development of various organs, such as leaves and seeds, in many species including soybean, chickpea, and tomato (Cookson et al, 2022;Naito et al, 2017;Nguyen et al, 2022;Swinnen et al, 2022), but that is absent in grasses (Schneider et al, 2021). Finally, mutations in DA1 and BIG BROTHER result in larger organs in Arabidopsis (Chen et al, 2021), but despite the conservation of these genes in maize, mutations in the corresponding maize genes, even resulting in similar changes in the conserved amino acids, fail to result in growth-related phenotypes (Gong et al, 2022b) (Fig.…”
Section: Plant Growth-regulatory Network and Their Translatabilitymentioning
confidence: 99%
“…Some growth‐regulatory networks only operate in eudicots and not in monocots, such as the PEAPOD‐KIX‐TOPLESS repressor complex (Schneider et al ., 2021) that restricts growth during the development of various organs (e.g. leaves and seeds) in many species including soybean, chickpea and tomato (Naito et al ., 2017; Cookson et al ., 2022; Nguyen et al ., 2022; Swinnen et al ., 2022), but that is absent in grasses (Schneider et al ., 2021). Finally, mutations in DA1 and BIG BROTHER result in larger organs in Arabidopsis (Chen et al ., 2021), but despite the conservation of these genes in maize, mutations in the corresponding maize genes, even resulting in similar changes in the conserved amino acids, fail to result in growth‐related phenotypes (Gong et al ., 2022b) (Fig.…”
Section: Plant Growth‐regulatory Network and Their Translatabilitymentioning
confidence: 99%